2001
DOI: 10.1354/vp.38-2-149
|View full text |Cite
|
Sign up to set email alerts
|

Pathobiology of A/Chicken/Hong Kong/220/97 (H5N1) Avian Influenza Virus in Seven Gallinaceous Species

Abstract: Abstract. Direct bird-to-human transmission, with the production of severe respiratory disease and human mortality, is unique to the Hong Kong-origin H5N1 highly pathogenic avian influenza (HPAI) virus, which was originally isolated from a disease outbreak in chickens. The pathobiology of the A/chicken/Hong Kong/ 220/97 (H5N1) (HK/220) HPAI virus was investigated in chickens, turkeys, Japanese and Bobwhite quail, guinea fowl, pheasants, and partridges, where it produced 75-100% mortality within 10 days. Depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
236
3
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(269 citation statements)
references
References 53 publications
24
236
3
1
Order By: Relevance
“…Similarly, H5N1 HPAIV has also been detected in feather follicles of gallinaceous species at 1 day p.i. (Perkins & Swayne, 2001). However, information on other HPAIV subtypes is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, H5N1 HPAIV has also been detected in feather follicles of gallinaceous species at 1 day p.i. (Perkins & Swayne, 2001). However, information on other HPAIV subtypes is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Procedures used to perform and interpret the IHC examination followed those previously described. 23 …”
Section: Histopathology and Immunohistochemistrymentioning
confidence: 99%
“…7,8 In contrast to low pathogenic avian Influenza A virus (LPAI virus) infection, in which replication is associated primarily with the mucosa of the gastrointestinal and respiratory tracts, 25 the H5N1 HPAI virus is found in multiple organs of infected birds. 2,25,31 The case fatality in chickens is ~100%, 9,11,14 while in ducks it is less severe and may not even induce clinical signs, 2,11,27,31 although some viruses have been reported to cause high fatality in ducks. 23,28 Findings have shown that the virus is able to replicate in feather structures of infected ducks and chickens, as indicated by either the isolation of virus or the presence of viral antigen in feather structures.…”
Section: Introductionmentioning
confidence: 99%
“…23,28 Findings have shown that the virus is able to replicate in feather structures of infected ducks and chickens, as indicated by either the isolation of virus or the presence of viral antigen in feather structures. 2,14,38,39 Several diagnostic methods, such as virus isolation (VI) and antigen and RNA detection tests, have been used to detect H5N1 virus in infected birds. 21,36 Oropharyngeal and cloacal swabs are the samples recommended for detecting avian influenza viruses, 17,34,36 and have been widely used for avian influenza surveillance.…”
Section: Introductionmentioning
confidence: 99%